Applications of Dynamic nuclear polarisation in biological systems - Deo, Thomas Sandeep (2021)
Cellular membrane disruption induced by the aggregation of amyloid beta (Aβ) peptide is considered a main mechanism responsible for neuronal death in Alzheimer’s disease. However, the molecular basis of this toxicity, in particular the interaction of Aβ and its aggregates with a cell membrane, remains unclear. Solidstate NMR (ssNMR) is a very well-suited technique for studies of the molecular basis of Aβ peptide interactions with cell membranes, but low sensitivity limits such studies due to a large fraction of the sample volume being taken up by lipids. Dynamic Nuclear Polarisation (DNP) allows increasing the signals in ssNMR experiments, thus enabling measurements with lower amounts of protein material. In this work, the feasibility of structural ssNMR-DNP studies of Aβ(1-40) peptide, at low concentration, interacting with biomimetic lipid bilayers was explored.